Perbandingan Hasil Belajar Siswa SMA Jaya Negara Melalui Model Pembelajaran Konvesional dan Model Kooperatif Tipe Jigsaw - Harti Oktarina; Herlina Herlina (Journal on Education, 2024)
This study is intended to identify there is no significant difference between the learning outcomes of students taught with the cooperative learning method of the type Jigsaw and the students learned with the conventional learning method in the Class X of the State Jaya High School of Makassar. This study involved all students in Jayanegara's 10th grade high school with a sample of 40 students. The sample consists of two classes, namely class XA as the experimental class and class XB as the control class. Testing learning results, documentation, and observation are the methods of data collection used. Based on the calculations of the pre-test data, the t test shows a count of 1,671, whereas the t-table is (0,05; 38) = 2,02439. Because of t-counting<t-table, that is 1,671 < 2.02439, it can be concluded that the abilities between the experimental class and the control class are not different. From the results of this study, the conclusion was drawn that there was a difference in the learning outcomes of students who used the cooperative learning method of Jigsaw with conventional methods. The authors suggest that teachers expand their knowledge and insight into innovative and creative learning approaches to improve the effectiveness of the teaching learning process